If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -8z = -15 Solving 1 + -8z = -15 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -8z = -15 + -1 Combine like terms: 1 + -1 = 0 0 + -8z = -15 + -1 -8z = -15 + -1 Combine like terms: -15 + -1 = -16 -8z = -16 Divide each side by '-8'. z = 2 Simplifying z = 2
| -y+6=11 | | 12x+5x=13x | | 2x-(x-5)=7-6(x-2) | | 48-6x=4x | | 5x+6y=6y+5x | | (9/10)*(4/5) | | -5x=4y+8 | | n+6=-16 | | 6s+s-4s-3s+4s=16 | | X^2+y^2+3x-2y=0 | | 5=3-(4-2) | | -4j-3j-j+j=20 | | 23=w+6 | | 1-2tan^2x=-tan^2x | | 0.25(y-4)+.03y=0.18y-0.05(40) | | j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) | | -3(3x-3)-9=-2(7x+3)-3 | | 16t^2+84t+112=0 | | 3x+6=27+y | | 7y+-42x+7=0 | | -8-6=7x-2-6x | | 6x-(8X+9)=2x-17 | | 9x+16y=-2 | | Sqrtx^2+7=x+1 | | 5*(x+8)=110 | | 26-u=234 | | 41.73/4.00x | | -4(3y+2x)= |